Structure and mechanical behavior of Big Area Additive Manufacturing (BAAM) materials. Issue 1 (16th January 2017) - Duty, Chad E.; Kunc, Vlastimil; Compton, Brett; Post, Brian; Erdman, Donald; Smith, Rachel; Lind, Randall; Lloyd, Peter; Love, Lonnie
Abstract : Purpose: This paper aims to investigate the deposited structure and mechanical performance of printed materials obtained during initial development of the Big Area Additive Manufacturing (BAAM) system at Oak Ridge National Laboratory. Issues unique to large-scale polymer deposition are identified and presented to reduce the learning curve for the development of similar systems. Design/methodology/approach: Although the BAAM's individual extruded bead is 10-20× larger (∼9 mm) than the typical small-scale systems, the overall characteristics of the deposited material are very similar. This study relates the structure of BAAM materials to the material composition, deposition parameters and resulting mechanical performance. Findings: Materials investigated during initial trials are suitable for stiffness-limited applications. The strength of printed materials can be significantly reduced by voids and imperfect fusion between layers. Deposited material was found to have voids between adjacent beads and micro-porosity within a given bead. Failure generally occurs at interfaces between adjacent beads and successive layers, indicating imperfect contact area and polymer fusion. Practical implications: The incorporation of second-phase reinforcement in printed materials can significantly improve stiffness but can result in notable anisotropy that needs to be accounted for in the design of BAAM-printed structures. Originality/value: This initial evaluation of BAAM-deposited structures and mechanical performance will guide the current research effort for improving interlaminar strength and process control.